PENGARUH brand ambassador ANDRE TAULANY TERHADAP MINAT BELI KONSUMEN “INI KERIPIK” - Jeki Setiawan Putra; N. Rachma; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACKThis research is to describe visibility, credibility, attraction, power and interest in buying and to know the influence visibility, credibility, attraction, power and interest in buying and partial buying interest, this research method uses quantitative methods. This type of research is explanatory research.The sample of this study was buyers of souvenir products "Ini Keripik" using purposive sampling, namely as many as 538 respondents with the determination of Slovin formula. Methods of collecting data using a questionnaire. The analytical method used in this study is SPSS 14.0 for windows multiple regression analysis.The results of this study indicate that : (1) there is a positive and significant effect of visibility on consumers' buying interest "Ini Keripik". (2) there is a positive and significant effect of credibility on consumers' buying interest “Ini Keripik". (3) there is a positive and significant influence on consumers' buying interest "Ini Keripik". (4) there is a positive and significant influence on consumer buying interest “Ini Keripik”.  Keywords : Visibility, Credibility, Attraction, Power, Interest in Buying